10.61533 ANALISIS PENGARUH SISTEM ADMINISTRASI PERPAJAKAN ONLINE, PEMERIKSAAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN DALAM MEMBAYAR PAJAK DI KPP PRATAMA KOTA PANGKALPINANG - Fransiska, Lisia; Tri Setyo Mulyani, Hendarti; Medinal (Jurnal Ilmiah Niaga Bisnis Elektronik, 2024)
This research uses a quantitative descriptive approach. The population in this study were all Corporate Taxpayers registered at KPP Pratama Pangkalpinang City, while the sample in this study was 84 Corporate Taxpayers registered at KPP Pratama Pangkalpinang City who met the research criteria. The research results show (1) the Online Tax Administration System has a partial effect on Corporate Taxpayer compliance with a significance value of 0.042 < 0.05 and a tcount value of 2.089 > than a ttable value of 1.675. (2) Tax audits have a partial effect on corporate taxpayer compliance with a significance value of 0.020 < 0.05 and a t value of 2.395 > than a t table value of 1.675. (3) Tax Sanctions have no partial effect on Corporate Taxpayer Compliance with a significance value of 0.067 > 0.05 and a tcount value of 1.869 > a ttable value of 1.675. (4) The online Tax Administration System, Tax Audits and Tax Sanctions simultaneously influence Corporate Taxpayer Compliance with a significance value of 0.001 < 0.05 and a fcount value of 31.586 > than a ftable value of 2.790